Cost effective use of free to use apps (FAN) in neurosurgery in developing countries: from clinical decision making to educational courses, strengthening the health care delivery - Amit Thapa (Society of Surgeons of Nepal, 2016)
Introduction and Objective: Financial limitations and scarcity of technological knowledge is a major hurdle to good communication platform, data storage and dissemination of medical knowledge in developing countries. Out of necessity we used free to use apps in our practice. We studied the applicability and cost effective aspect of a systematic use of these apps in neurosurgery.